Agitation and Sugar Craving Related to Epilepsy Seizure - Rania Adel Hameed; Mohammad Reza F. Aghdam (Case Reports in Psychiatry)
Introduction. Epilepsy is a chronic central nervous system disorder characterized by the recurrence of unprovoked seizures and can affect people of all ages. Seizure symptoms can vary widely in patients. Many papers have been published about agitation and epileptic seizures, but almost nothing about sugar cravings and agitation related to epilepsy. The purpose of this case report is to shed light on possibly a hidden symptom within the epilepsy field, in fact sugar cravings. Case presentation. A 12-year-old boy was referred to the children and adolescent psychiatric outpatient clinic with suspicion of ADHD. The boy has struggled with anxiety, concentration, and impulsivity. Because of intense agitation and sugar cravings, the patient was referred to EEG. The EEG shows pathological activity with bilatero-temporal to central epileptiform activity, not synchronized. After pathological EEG findings, the patient started treatment with Lamotrigine. Great improvement when it comes to agitation, moodiness, and reduction of sugar craving after starting with Lamotrigine. Conclusion. We consider inexplicable behavior or symptoms such as agitation and sugar craving may be related to epilepsy seizure. Therefore, it is important that these patients should be examined more closely with EEG to confirm or deny epilepsy.